Managing tomato leaf curl virus - Singh, R K; Rai, N; Singh, Major (Indian Horticulture, 2015)
Today, it is difficult for tomato producers and breeders to manage ToLCV disease in tomato crops by using chemical pesticides. If producers/breeders adopt best screening procedure by vector inoculation, biochemical and physiological analysis, and using molecular markers or well planed breeding procedure or follow all control measures, then they can be obtained easily.